Operational Pitch Actuation Dynamics for Offshore Wind Turbines Ranging from 5 to 50 MW - Michael Jeong; Eric Loth; Chris Qin; Mandar Phadnis; Manuel Pusch; Lucy Pao (Wind Energy)
ABSTRACT Modern wind turbines have been continuously growing in size due to the increased power generation and reduced costs associated with larger rotors and more abundant wind resources offshore. In order to effectively implement pitch control on blades that are longer, more flexible, and heavier than ever before, modern electric pitch systems must provide enough torque to overcome blade pitch inertia and loads while providing suitable control response frequencies. Despite this need, there is limited published research on the sizing of such pitch systems at extreme scales. This study models peak pitching power and pitch actuator torque requirements in Regions 2 and 3 turbulent wind conditions. The developed model considers blade pitch response, pitching moments, pitch system dynamics, and blade aeroelasticity. The model is applied using an integrated wind turbine code used to simulate the turbine response of a 25‐MW offshore reference turbine with advanced pitch control under standardized turbulent wind conditions. The results show that the fastest pitch response requirements occur in Region 3 wind speeds just above the rated wind speed and that the peak pitch actuator torque requirements are correlated with maximum pitching moments. The model is extended to turbines ranging from 5 to 50 MW to develop a simplified scaling power law based on only the product of blade mass and mean chord length. This scaling law predicts maximum pitch actuator torque and maximum power consumed from pitch actuation based on results from computational simulations of multiple extreme‐scale reference turbines. This study provides useful insights for the design and sizing of pitch systems in large‐scale wind turbines.